Current Behaviours and Future Prospects of Online Film Consumption in China: A Social Marketing Perspective - Zhuang, Yunhong (2013)
Free film downloading services have gained large popularity among Chinese consumers, although there is potential film copyright losses as many of the downloading resources offer pirated films. Based on previous studies of consumer behaviour theory, social marketing and film piracy, this research was an attempt to gain an understanding of the factors that influence consumer film downloading and to discuss the role of social marketing in changing such behaviour through promoting paid online film service.